A Bioeconomic Projection of Climate‐Induced Wildfire Risk in the Forest Sector. Issue 4 (22nd April 2022) - Riviere, M.; Pimont, F.; Delacote, P.; Caurla, S.; Ruffault, J.; Lobianco, A.; Opitz, T.; Dupuy, J. L.
Abstract: Under the influence of climate change, wildfire regimes are expected to intensify and expand to new areas, increasing threats to natural and socioeconomic assets. We explore the environmental and economic implications for the forest sector of climate‐induced changes in wildfire regimes. To retain genericity while considering local determinants, we focus on the regional level and take Mediterranean France as an example. Coupling a bioeconomic forest sector model and a model of wildfire activity, we perform spatially explicit simulations under various levels of radiative forcing. By using a probabilistic framework, we also assess the propagation of several sources of uncertainty to the forest sector, considering both climate‐induced uncertainty and the intrinsic stochasticity of the fire process. By the end of the century, summer burned areas increase by up to 55%, causing moderate losses of merchantable timber and forest carbon stocks, with cascading impacts for industrial activities and climate mitigation in the forest sector. Implications for industries remain limited, but we observe price increases, especially for softwoods, as well as spatially differentiated changes in producer welfare. Inter‐annual fluctuations explain most of uncertainty in wildfire activity, but their impacts on the forest sector are quickly dampened. Over time, owing to the cumulative nature of wildfire impacts on forest resources, uncertainty related to climate warming, climate models' response and stochasticity intrinsic to the wildfire phenomenon strongly increase in relative importance. Results reassert the need to consider multiple futures in prospective assessments, including uncertainty inherent to natural processes, often omitted in large‐scale economic assessments. Plain Language Summary: Forest fires in the Mediterranean are expected to become more numerous, more intense, and to reach new areas due to climate change. Forest resources, carbon sequestrated in forests, as well as economic activities related to forestry, are threatened by this evolution. This article focuses on Southern France and uses large‐scale model simulations to explore these dynamics. We show that burned areas in forests may increase by more than half by 2100, leading to a decrease in forest resources (timber) by up to 5%. Besides, prices for wood products may increase, especially for softwoods, with implications for the welfare of timber producers and consumers. Moreover, these results are heterogenous across space, and areas to the south and to the west are more gravely affected. However, these trends come with relatively large uncertainties. We show that uncertainties concerning the evolution of forest fires themselves are largely due to annual variability in weather conditions. On the contrary, uncertainties concerning economic activity in forestry are mostly due to the unknown future evolution of greenhouse gas emissions and to differences in climate models functioning. Our results reassert the need to consider several possible sources of uncertainty in long‐term prospective assessments. Key Points: Models project an intensification of wildfire regimes in southern France, losses of forest resources and carbon, disturbances to forestry Uncertainty in projections is dominated by annual fluctuations for wildfire activity, by choice of climate model/scenario for forestry Prospective bioeconomic assessments need to consider multiple possible futures but also stochasticity intrinsic to disturbance processes